2015
DOI: 10.1371/journal.pone.0121078
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Posttraumatic Pseudoaneurysms in Patients Treated with Nonoperative Management for Blunt Abdominal Solid Organ Injuries

Abstract: BackgroundPosttraumatic pseudoaneurysms (PAs) have been recognized as the cause of delayed hemorrhage complicated with nonoperative management (NOM), although the need for intervention in patients with small-sized PAs and the relationship between the occurrence of PAs and bed-rest has been also unclear.ObjectivesThe purpose of this study was to investigate the clinical history of small-sized PAs (less than 10 mm in diameter) which occurred in abdominal solid organs, and to analyze the relationship between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
2
13
1
Order By: Relevance
“…In the absence of long-term data, it is prudent to treat them. This is consistent with prior studies that demonstrate spontaneous resolution of most hepatic post traumatic pseudoaneurysms [19].…”
Section: Discussionsupporting
confidence: 93%
“…In the absence of long-term data, it is prudent to treat them. This is consistent with prior studies that demonstrate spontaneous resolution of most hepatic post traumatic pseudoaneurysms [19].…”
Section: Discussionsupporting
confidence: 93%
“…Because our cases had a diameter of < 10 mm and were surrounded by the liver parenchyma within the intrahepatic parenchyma, we chose to treat conservatively. Kittaka et al reported that post-traumatic pseudoaneurysm in solid organs, such as the liver, spleen, and kidney, may disappear spontaneously when the diameter is < 10 mm [ 21 ]. Even if the HAPs rupture, it might be possible that hemostasis could still be obtained by internal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the rates of delayed hemorrhage though rare, occur in 0–3.9% of patients. It is a life-threatening complication of NOM and often requires an emergency laparotomy and needs to be judiciously undertaken with explained risks [ 11 ].…”
Section: Discussionmentioning
confidence: 99%